2012
DOI: 10.7235/hort.2012.11090
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Application on Standard Chrysanthemum Alleviates Damages Induced by Disease and Aphid Insect

Abstract: To elucidate the role of silicon in biotic stress such as pests and diseases, standard chrysanthemum was grown in pots filled with soil without application of pesticide and fungicide. Si treatment was largely composed of three groups: K2SiO3 (50, 100, and 200 mg・L-1), three brands of silicate fertilizer (SiF1, SiF2, and SiF3) and tap water as a control. Si sources were constantly drenched into pots for 14 weeks. Application high concentration K2SiO3 (200 mg・L-1) and three commercial Si fertilizers for 14 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…As mentioned previously, these differences may be due to the growing system (soilless substrate vs. hydroponics), Si application method, environmental growth conditions, or cultivar. Other floricultural crops, including low and high Si accumulators, have also exhibited an increase in foliar Si in response to potassium silicate supplementation (hydroponic or drench application), including snapdragon 'Bedding Rocket White' (Frantz et al, 2011), rose (Rosa hybrida 'Meipelta') (Gillman et al, 2003), chrysanthemum (Dendranthema grandiflorum 'Shinro') (Jeong et al, 2012), gerbera (Gerbera hybrid L. 'Acapella') (Kamenidou et al, 2010), sunflower 'Ring of Fire' (Kamenidou et al, 2008(Kamenidou et al, , 2011, and zinnia 'Oklahoma Formula Mix' (Kamenidou et al, 2009). Highest Si concentrations in Sisupplemented plants were localized in roots, followed by leaves, and then lower (but similar) values in flowers and stems (analysis not shown).…”
Section: Si Cultivar Zmentioning
confidence: 99%
“…As mentioned previously, these differences may be due to the growing system (soilless substrate vs. hydroponics), Si application method, environmental growth conditions, or cultivar. Other floricultural crops, including low and high Si accumulators, have also exhibited an increase in foliar Si in response to potassium silicate supplementation (hydroponic or drench application), including snapdragon 'Bedding Rocket White' (Frantz et al, 2011), rose (Rosa hybrida 'Meipelta') (Gillman et al, 2003), chrysanthemum (Dendranthema grandiflorum 'Shinro') (Jeong et al, 2012), gerbera (Gerbera hybrid L. 'Acapella') (Kamenidou et al, 2010), sunflower 'Ring of Fire' (Kamenidou et al, 2008(Kamenidou et al, , 2011, and zinnia 'Oklahoma Formula Mix' (Kamenidou et al, 2009). Highest Si concentrations in Sisupplemented plants were localized in roots, followed by leaves, and then lower (but similar) values in flowers and stems (analysis not shown).…”
Section: Si Cultivar Zmentioning
confidence: 99%
“…However, recent studies have shown that the Si nutrition enhanced growth traits in carnation (Bae et al, 2010), chrysanthemum 'Backwang' (Moon et al, 2008), gerbera (Kamenidou et al, 2010;Savvas et al, 2002), kalanchoe (Bae et al, 2010), sunflower (Kamenidou et al, 2008), rose (Ehret et al, 2005;Hwang et al, 2005), and zinnia (Kamenidou et al, 2009). Furthermore, application of Si has been shown to be able to control diseases (Rodrigues et al, 2003;Voogt and Sonneveld, 2001) and pests (Jeong et al, 2012;Ranganathan et al, 2006), alleviate toxicity of some heavy metals (Shi et al, 2010), and enhance resistance to drought (Chen et al, 2011), salinity (MateosNaranjo et al, 2013), and temperature stresses (Epstein, 1999;Ma and Yamaji, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding Si mediated resistance to insect pests, potassium silicate drenches at 200 mg.L -1 Si or greater reduced leafminer (Liriomyza trifolii) emergence from infected Chrysanthemum plants (PARELLA et al, 2007). A 40 to 57% reduction in naturally occurring aphid (Macrosiphoniellas anborni) colonies was noted in Si treated Chrysanthemum plants as compared with control plants without Si (JEONG et al, 2012). Potassium silicate drenches led to modest yet significant reductions in fecundity of green peach aphids (Myzus persicae) feeding on Zinnia elegans (RANGER et al, 2009).…”
Section: Plant Biotic/abiotic Stress Tolerancementioning
confidence: 98%
“…Calcium silicate supplementation decreased Botrytis infection of Helianthus annuus 'Ring of Fire ' (KAMENIDOU et al, 2002). Potassium silicate as well as three other commercially available Si fertilizers reduced naturally occurring disease incidence of Chrysanthemum 'Shinro' when examined 14 days after transplanting (JEONG et al, 2012). Potassium silicate drenches as well as two organic substrate amendments containing Si, rice (Oryza sativa) hulls and chopped Miscanthus x giganteum) straw reduced incidence of powdery mildew on Zinnia elegans up to 8 weeks after inoculation with the disease (LOCKE et al, 2010).…”
Section: Plant Biotic/abiotic Stress Tolerancementioning
confidence: 99%